THE ISSUE OF RADICALISM IN THE INTERPRETATION OF THE QUR'AN: AN ANALYSIS OF JIHAD VERSES AND TOLERANCE IN CONTEMPORARY INDONESIAN INTERPRETATION - Mukti, Anwar; Fathoni, Ahmad Nur; Hakim, M. Luqman; Cahyono, Agung Mandiro; Bahrudin, Moh.; Widiyaningrum, Kuni Maftukhati (West Science Islamic Studies, 2024)
Religious radicalism in Indonesia is often rooted in an interpretation of Qur'anic verses that are not comprehensive and taken out of context, especially those on jihad and tolerance. This article analyzes the issue of radicalism through a study of the interpretation of these verses in contemporary Indonesian interpretation, by examining Tafsir Al-Azhar, Tafsir Al-Misbah, as well as modern hermeneutical approaches such as ma'na--maghzā. The results of the study show that Indonesian mufassir affirms the meaning of jihad as a moral and spiritual struggle, not a legitimacy of violence. Meanwhile, the verses of tolerance are understood as the theological foundation for harmonious relations between religions in a pluralistic society. Previous research has also emphasized the importance of religious moderation and the role of educational institutions in preventing radicalism through the teaching of contextual and balanced interpretations. This article concludes that a comprehensive and moderate interpretation of the Qur'an is an important instrument in efforts to deradicalize and strengthen social harmony in Indonesia.